Parents' and child characteristics in relation to prental involvement in children's schooling. - Panganiban, Rosario P
This study sought to find out the strength and direction of relationship between and among parental involvement and its predictors. Parents' perceived self-efficacy, parents' expectation, birth order and child academic achievement were hypothesized to influence the degree of parental involvement. Fifty-two parents were chosen from the population through purposive random sampling. Different scales were used to measure parental involvement, expectation and self-efficacy. Multiple correlation showed that there was a significant correlation between parental involvement and efficacy (r = .232; p_ < .05), parental involvement and grade ( r = .361; p_ < .05) and birth order and expectation (r = .242; p_ < .05). The test for two independent means further revealed that parents with high parental involvement have children with good academic standing compared to children with low parental involvement.